2017
DOI: 10.1080/14728222.2017.1386174
|View full text |Cite
|
Sign up to set email alerts
|

Open-angle glaucoma: therapeutically targeting the extracellular matrix of the conventional outflow pathway

Abstract: Introduction:Ocular hypertension in open-angle glaucoma is caused by a reduced rate of removal of aqueous humour (AH) from the eye, with the majority of AH draining from the anterior chamber through the conventional outflow pathway, comprising the trabecular meshwork (TM) and Schlemm's Canal. Resistance to outflow is generated, in part, by the extracellular matrix (ECM) of the outflow tissues. Current pressure-lowering topical medications largely suppress AH production, or enhance its clearance through the unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 170 publications
0
33
0
Order By: Relevance
“…In humans, IOP is primarily controlled by the out‐flow of the AH through the trabecular meshwork (TM), also known as the conventional out‐flow pathway. The TM is a porous structure composed of endothelial cells embedded in a dense extracellular matrix (ECM), composed of collagen, elastic fibres, proteoglycans and other macromolecules . Fibrotic changes or deposits of ECM into the TM can slow or block the out‐flow which leads to an elevation of the IOP .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, IOP is primarily controlled by the out‐flow of the AH through the trabecular meshwork (TM), also known as the conventional out‐flow pathway. The TM is a porous structure composed of endothelial cells embedded in a dense extracellular matrix (ECM), composed of collagen, elastic fibres, proteoglycans and other macromolecules . Fibrotic changes or deposits of ECM into the TM can slow or block the out‐flow which leads to an elevation of the IOP .…”
Section: Introductionmentioning
confidence: 99%
“…Fibrotic changes or deposits of ECM into the TM can slow or block the out‐flow which leads to an elevation of the IOP . Glaucoma is thus linked to TM structure and function where structural changes in the TM likely alter tissue architecture and biomechanical properties which, in turn, influence its resistance to AH out‐flow …”
Section: Introductionmentioning
confidence: 99%
“…33 The ECM of the juxtacanalicular region participates in the generation of resistance to aqueous humor outflow through the TM pathway. 31 The ECM of the TM consists of collagens, laminins, elastin, fibronectin, fibrillins, and proteoglycans 34 and is continuously being remodeled by members of the MMP family (eg, MMP-1, -2, -3, -9, -12, and -14). 12 Studies using perfused human anterior segment organ cultures and human TM cell cultures have shown that increases in IOP cause an increase in MMP-2 expression, and mechanical stretching of TM cells causes an increase in MMP-2 expression and a decrease in TIMP-2 expression.…”
Section: Glaucoma Aqueous Outflow Pathways and Mmpsmentioning
confidence: 99%
“…Increased intraocular pressure is considered to be the most important risk factor for the incidence and progression of glaucoma [4,[7][8][9]]. An imbalance between aqueous humor secretion in the ciliary body (CB) and outflow in the anterior chamber angle mainly due to increased outflow resistance is responsible for the increased IOP in glaucoma [10,11]. However, little is known about the exact mechanisms of IOP regulation.…”
Section: Discussionmentioning
confidence: 99%